„O zachowaniu się przy stole”, czyli językowa kreacja obyczajów biesiadnych w Krzyżakach Henryka Sienkiewicza - Mariak, Leonarda (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The present article contains a linguistic and stylistic analysis of the presentation of table manners and table etiquette as it is described in Krzyżacy [The Knights of the Cross] by Henryk Sienkiewicz. The article consists of three parts which successively describe the most important elements of medieval cuisine (courses, beverages and spices). Some attention has also been paid to the dishes and good manners at the table. The analysis of the collected lexical material shows that the festive manners, courses, beverages and dishes presented in the novel complete the credibility of other realities of medieval everyday life described in the novel, such as clothes, furnishings of Medieval houses and entertainment. Taking into account the minimal number of historical sources dedicated to everyday life of Medieval Polish people, the world of festive manners and the cuisine created by Henryk Sienkiewicz, which is close to medieval reality, came into existence mainly thanks to the writer’s imagination and language intuition.